Five-year Trends in Opioid Prescribing Following Orthopaedic Trauma. (August 2020) - Flanagan, Christopher D.; Joseph, Noah M.; Benedick, Alex; Vallier, Heather A.
Abstract : Introduction: Legislatures across the country are passing new opioid prescribing laws. To understand the effects of this legislation, baseline autonomous shifts in physician opioid prescribing must be evaluated. Methods: The purpose of this retrospective dual cohort comparison study was to evaluate 5-year opioid prescribing trends in orthopaedic trauma patients. Demographic and injury information were collected on adult trauma patients with surgically managed orthopaedic fractures from 2012 (N = 190) and 2017 (N = 160). The amount of opioid medication prescribed from discharge to 1 year after the injury was collected. Opioid prescriptions were converted to morphine milligram equivalents (MMEs). The main outcome measure was opioid medication prescribed in 2017 versus 2012. Results: The cohorts were well-matched on sex, race, medical comorbidities, substance use, fracture location, Injury Severity Score, hospital length of stay, and intensive care unit admission metrics. However, the 2012 cohort was older than the 2017 cohort (51.9 versus 43.3 years, P < 0.001). When controlling for age, total opioid medication prescribed was greater in 2012 than in 2017 (1, 680 versus 1, 110 MME, P = 0.001). Patients in 2017 received both lower discharge prescriptions (523 versus 407 MME, P < 0.001) and lower total opioid prescription refill amounts (1, 140 versus 766 MME, P = 0.037). The number of refills prescribed was equal, but patients received lower amounts of opioid medications per refill in 2017 (333 versus 243 MME, P < 0.001). Despite these differences, the percentage of patients ceasing prescription opioid use 1 year after injury was unchanged (90.6% versus 92.1%, P = 0.675). Discussion: Over 5 years, providers have successfully reduced the amount of opioid medication prescribed to surgically managed orthopaedic trauma patients through self-directed measures. The effects of opioid prescribing legislation should be viewed from this baseline.